Changes of whole-body power, muscle function, and jump performance with prolonged cycling to exhaustion - McIntyre, J. P. R.; Mawston, G. A.; Cairns, S. P. (International Journal of Sports Physiology and Performance, 2012)
Purpose: To quantify how whole-body power, muscle-function, and jump-performance measures change during prolonged cycling and recovery and determine whether there are relationships between the different fatigue measures. Methods: Ten competitive or recreationally active male cyclists underwent repeated 20-min stages of prolonged cycling at 70% VO2peak until exhaustion. Whole-body peak power output (PPO) was assessed using an all-out 30-s sprint 17 min into each cycle stage. Ratings of perceived exertion (RPE) were recorded throughout. Isometric and isokinetic muscle-function tests were made between cycle stages, over ~6 min, and during 30-min recovery. Drop-jump measures were tested at exhaustion and during recovery. Results: PPO initially increased or was maintained in some subjects but fell to 81% of maximum at exhaustion. RPE was near maximal (18.7) at exhaustion, with the time to exhaustion related to the rate of rise of RPE. PPO first started to decline only when RPE exceeded 16 (ie, hard). Peak isometric and concentric isokinetic torque (180°/s) for the quadriceps fell to 86% and 83% of pretest at exhaustion, respectively. In contrast, the peak concentric isokinetic torque (180°/s) of the hamstrings increased by 10% before declining to 93% of maximum. Jump height fell to 92% of pretest at exhaustion and was correlated with the decline in PPO (r = .79). Muscle-function and jump-performance measures did not recover over the 30-min postexercise rest period. Conclusions: At exhaustion, whole-body power, muscle-function, and jump-performance measures had all fallen by 7-19%. PPO and drop-jump decrements were linearly correlated and are appropriate measures of maximal performance.